Intra-abdominal bleeding during treprostinil infusion in a patient with pulmonary arterial hypertension. (27th February 2013) - Mindus, Stephanie; Pawlowski, Jacek; Nisell, Magnus; Ferrara, Giovanni
Abstract : Medical treatment of pulmonary arterial hypertension (PAH) is increasingly common. Prostacyclins were introduced in the early 90s, and treprostinil is one of the most frequently used drugs of this class today, owing to its long half-life and to the possibility to administer the molecule through several routes. Treprostinil is considered a safe drug and is associated with a significant improvement of exercise capacity, especially in patients with idiopathic PAH (iPAH). Systemic sclerosis-associated PAH (sc-PAH) correlates to a worse prognosis compared with that of iPAH. Despite these considerations, safety data on treprostinil are still limited and mainly derived from randomised controlled trials and retrospective studies with relatively small and heterogeneous cohorts of patients with PAH. We report the occurrence of a severe intra-abdominal bleeding during treprostinil infusion in a patient with sc-PAH.